Implementation and impact of halal food standard: an empirical study in Malaysia - Sari, Dian Permata; Jaswir, Irwandi; Haji Che Daud, Mohd. Radzi (Bank Sentral Republik Inonesia, 2021)
As a Malaysian Halal Food Standard, MS1500 is established to strengthened Malaysian role in the global halal market. This study aims to identify the factors affecting the implementation of MS1500, the positive impact of this implementation and the relationship between the implementation and its impact. Food and Beverages Industry in Malaysia which already got Halal Certificate and Halal Logo was chosen as scope of population. This study applied Covariance-Based Structural-Equation-Modelling (CB-SEM) method with 212 sample companies. The results showed that Perception-On-Implementation, Halal-Control-System-Activity and Owner-Management-Employee-Limitation are the factors affecting the Implementation of MS1500. It is also found four Positive Impact of Implementation of this MS: Trade & Free Movement, Innovation, Clean & Save Production-Process and Consumer & Corporate Image. Additionally, this study discovered that the better the implementation of MS 1500, the higher the positive impact that can be accomplished by the industry. It is also found that in Malaysia, finance and regulation were not the factors that cause the limitation on implementation of Halal Food Standard. Finding of this study can be used as an input for Malaysian government in planning any suitable programme to promote the implementation of this standard. Additionally, the extent of the positive impacts of this implementation for the industry is expected to be able to encourage all food industry in Malaysia to apply and fully implement this MS in their daily operations.